Waste Processing as Organic Compost Fertilizer Using Smart Composter in Sei Ular Village, Secanggang District, Langkat Regency - Sadeli, Achmad; Nasution, Tulus Ikhsan (Journal of Saintech Transfer, 2022)
The activity was carried out in Sei Ular Village, Secanggang District, Langkat Regency from May - November 2021. The problems faced by partners are 1) The price of chemical fertilizers is relatively expensive and difficult to obtain. 2) Continuous use of chemical fertilizers destroys soil quality 3) There is a lot of unused agricultural and livestock waste. 4) People don’t know what kind of waste can be used as compost. 5) People don’t know how to process compost using smart composters. The purposes of implementing this activity are 1) The community can process agricultural and livestock waste into organic compost 2) The community can get fertilizer at a cheaper price and easily to obtained 3) Improve soil nutrients at the service location 4) to increase the income of the farmer. The results are in the form of training and mentoring services for making organic compost with the help of a smart composter. The approach method is carried out by overcoming partner problems and then resolving the problem through an activity program by referring to the science and technology approach. The results obtained after the implementation of counseling and training obtained that 85.71% of participants were interested in making compost by utilizing waste. The public feels organic compost fertilizer does not require too large a cost because it can utilize waste around the community.